The relationship between entrepreneurship and sustainable development in Saudi Arabia: A comprehensive perspective - Lena Bedawi Elfadli Elmonshid; Omer Ahmed Sayed (Economies, 2024)
This study examines the relationship between entrepreneurship and sustainable development in Saudi Arabia from 2006 to 2022, focusing on the economic, social, and environmental dimensions. Using the autoregressive distributed lag (ARDL) model, the research investigates both short-run and long-run dynamics to understand how entrepreneurial activities influence sustainable development within the framework of Saudi Arabia's Vision 2030 initiative. The findings indicate that entrepreneurship significantly contributes to economic growth through job creation and innovation, thereby aiding in the diversification of the economy away from oil dependency. Socially, entrepreneurial initiatives have a positive impact on gender equality and social inclusion by empowering women and integrating youth into the labor market. Environmentally, entrepreneurship helps reduce carbon emissions and promotes sustainable business practices. Despite these positive outcomes, challenges such as regulatory barriers, limited access to finance, and the need for a supportive entrepreneurial ecosystem remain. Recommendations include enhancing entrepreneurial education, providing financial incentives, and streamlining regulatory processes to better support start-ups and SMEs. This study highlights the necessity of addressing these challenges to fully realize the potential of entrepreneurship for sustainable development in Saudi Arabia. By providing empirical evidence on the significant role of entrepreneurship in driving sustainable development, this research offers actionable insights for policymakers aiming to foster a more resilient and diversified economy in line with Vision 2030.
Keywords: 330; entrepreneurship; economic growth; ARDL model; environmental sustainability; sustainable development